2016
DOI: 10.3847/0004-637x/830/2/102
|View full text |Cite
|
Sign up to set email alerts
|

A SEARCH FOR O2 IN CO-DEPLETED MOLECULAR CLOUD CORES WITH HERSCHEL

Abstract: The general lack of molecular oxygen in molecular clouds is an outstanding problem in astrochemistry. Extensive searches with SWAS, Odin and Herschel have only produced two detections; upper limits to the O 2 abundance in the remaining sources observed are about 1000 times lower than predicted by chemical models. Previous atomic oxygen observations and inferences from observations of other molecules indicated that high abundances of O atoms might be present in dense cores exhibiting large amounts of CO depleti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Of considerable interest is to understand the formation history of O 2 in ρ Oph A as this molecule, in spite of numerous attempts (Goldsmith et al 2000(Goldsmith et al , 2002Pagani et al 2003;Yıldız et al 2013;Sandqvist et al 2015;Wirström et al 2016), has hardly been found anywhere else outside the solar system. Taking into account new lab results for the oxygen binding energy on dust grains (He et al 2015), Taquet et al (2016) recently discussed a number of formation scenarios and argued in favour of a particular one that could fit the physical conditions in ρ Oph A.…”
Section: Abundant O 2 Production In ρ Oph Amentioning
confidence: 99%
“…Of considerable interest is to understand the formation history of O 2 in ρ Oph A as this molecule, in spite of numerous attempts (Goldsmith et al 2000(Goldsmith et al , 2002Pagani et al 2003;Yıldız et al 2013;Sandqvist et al 2015;Wirström et al 2016), has hardly been found anywhere else outside the solar system. Taking into account new lab results for the oxygen binding energy on dust grains (He et al 2015), Taquet et al (2016) recently discussed a number of formation scenarios and argued in favour of a particular one that could fit the physical conditions in ρ Oph A.…”
Section: Abundant O 2 Production In ρ Oph Amentioning
confidence: 99%
“…reflecting the abundances in the nascent molecular clouds from which the comets formed) then the high O2 abundances that are detected in comet 67P/C-G would seem to be at odds with both observations and (equilibrium) astrochemical models; which predict O2 abundances of at least an order of magnitude lower in dark clouds than these values (e.g. Wirström, Charnley, Cordiner & Ceccarelli 2016), although there may be an obvious reason for this -as discussed above.…”
Section: A Primordial Origin For the O2mentioning
confidence: 94%
“…Yildiz et al 2013) have found that the depletion of O-atoms by freeze-out and conversion to H2O and/or the destruction of O2 by C-atoms (before CO formation is complete) yields low values of the O2 abundance -typically an order of magnitude or more smaller than what is found in comet 67P/C-G. However, these models also show that the O2 abundance rises significantly after the efficient conversion of C to CO has occurred (Wirström, Charnley, Cordiner & Ceccarelli 2016). Moreover, the models also assume that the freeze-out of O-atoms and conversion to H2O, which is fully retained in the ices is efficient.…”
Section: A Gas-phase Primordial Origin Of O2mentioning
confidence: 98%
See 1 more Smart Citation
“…However, O 2 is difficult to detect, and it is commonly believed that it is not a major repository of oxygen in molecular clouds. In only two sources has molecular oxygen been identified so far, namely ρ Oph A and Orion A (Larsson et al 2007;Liseau et al 2012;Goldsmith et al 2011;Chen et al 2014), and many further attempts to find it in the gas phase have failed (Goldsmith et al 2000;Melnick & Bergin 2005;Yildiz et al 2013;Wirström et al 2016), as did the attempts to find it in solid form (Van den Bussche et al 1999;Tielens 2000).…”
Section: Introductionmentioning
confidence: 99%